Identification of Patterns on Asdic Records - Stubbs, A. R. (The International Hydrographic Review, 2015)
An asdic record obtained to give information about one facet of the underwater environment can also provide information about other facets and the record can be confused by acoustic and electrical noise from a number of sources. This paper indicates the origin of some of these signals and attempts to promote an awareness in those concerned with asdic records of the unusual aspects that may arise.